Contextual factors triggering placebo and nocebo effects in nursing practice: Findings from a national cross‐sectional study. Issue 9 (18th February 2019) - Palese, Alvisa; Cadorin, Lucia; Testa, Marco; Geri, Tommaso; Colloca, Luana; Rossettini, Giacomo
Abstract: Aims and objectives: To describe contextual factors (CFs) used by nurses to increase placebo and to prevent nocebo effects. Background: Placebo effects have been studied in the nursing discipline, but nocebo effects still remain unexplored. Recently, a set of CFs functioning as triggers of placebo/nocebo effects has been described; however, its use in daily care has never been documented to date. Design: A national cross‐sectional survey, according to the Checklist for Reporting Results of Internet E‐Surveys guidelines and STrengthening the Reporting of OBservational Studies in Epidemiology (STROBE), was performed in 2016. Methods: A wide sample of Italian nurses belonging to four national associations was involved. A questionnaire based on CFs literature was developed and administered through the SurveyMonkey Software ® exploring: (a) CFs definition, (b) beliefs, (c) case‐by‐case frequency of use, (d) circumstances of application, (e) clinical conditions where participants perceived their potential beneficial effects, (f) ethical implications and (g) communication issues with the patient. Results: Out of 1, 411 eligible nurses, 455 answered (32.2%) and 425 questionnaires (30.1%) were valid for the analysis. A total of 211 nurses (49.6%) defined the CFs as an intervention with a possible aspecific effect; participants believed in the CFs (2.91; 95%CI 2.88–2.94), using them >2 times/month, mainly in addition to a nursing intervention to optimise clinical outcomes ( n = 79; 18.6%). Psychological and physiological therapeutic effects have been perceived mainly in chronic pain ( n = 259; 60.9%) and insomnia ( n = 243; 57.2%). According to participants, CFs have been reported as ethically acceptable when exerting beneficial psychological effects ( n = 148; 34.8%); however, 103 (24.2%) of nurses did not communicate to the patient when CFs were used. Conclusions: Nurses are aware of CFs as elements to increase the placebo and prevent the nocebo effects in concomitance with evidence‐based nursing interventions. Relevance to clinical practice: The CFs valued by nurses and experienced as effective are mainly based upon the internal quality of the nurse and the quality of the relationship between the nurse and the patient. These qualities require a large personal investment; therefore, nurses should be supported in developing these qualities since their nursing graduation.